Changing role of caste associations - Verma, K. K. (New Delhi, 1979)
The book is a case study of the Caste Associations (Jati Sabhas) of the Kurmi. The study presents a micro sociological observation of the Kurmi Sabhas in North India and their role in the process of social transformation. The study highlights the changing behaviour of the Kurmi Sabhas. The author has shown how the Kurmi have evolved a supra-local and supra ethnic network. The role of traditional and emergent leaderships in the organisation and the relationship bet ween them and the masses have also been discussed. The study is based on documentary sources, personal interviews and participant observation.
Keywords: Sociology